Characterization of Indonesian pigmented rice (Oryza sativa) based on morphology and Single Nucleotide Polymorphisms - NUR SITI KURNIASIH; RATNA SUSANDARINI; FEBRI ADI SUSANTO; TRI RINI NURINGTYAS; GLYN JENKINS; YEKTI ASIH PURWESTRI (Society for Indonesian Biodiversity, 2019)
Abstract. Kurniasih NS, Susandarini R, Susanto FA, Nuringtyas TR, Jenkins G, Purwestri YA. 2019. Characterization of Indonesian pigmented rice (Oryza sativa) based on morphology and Single Nucleotide Polymorphisms. Biodiversitas 20: 1208-1214. Indonesia has many cultivars of pigmented rice, but many variants have not been characterized using morphological characters and molecular markers. SNPs (Single Nucleotide polymorphisms) have been used in previous studies to identify the Indica and Japonica subspecies. Characterization of whether a line belongs to the Indica or Japonica subspecies is useful information for rice breeders, especially to generate line exhibiting the strong hybrid vigor. Morphological characters are used to determine the relationship between cultivars using cluster analysis. The SNP markers were amplified by PCR, sequenced and compared with sequences in the GenBank. Based on morphological characters, ten cultivars divide into two clusters. SNPs distinguish Indica and Japonica subspecies, and show that Hitam Lampung, Aek Sibundong, Melik, Hitam Toraja, Merah Kalimantan, and Merah Sumbawa belong to the Indica subspecies while Cempo Ireng and Pare Eja belong to Japonica. Abang Segreng and Hitam Toraja could not be clearly assigned to either the Indica or Japonica subspecies.